Multifactoriality of Parkinson’s Disease as Explored Through Human Neural Stem Cells and Their Transplantation in Middle-Aged Parkinsonian Mice - Nelke, Anna; García-López, Silvia; Martínez-Serrano, Alberto; Pereira, Marta P. (Frontiers in Pharmacology, 2022)
Parkinson´s disease (PD) is an age-associated neurodegenerative disorder for which there is currently no cure. Cell replacement therapy is a potential treatment for PD; however, this therapy has more clinically beneficial outcomes in younger patients with less advanced PD. In this study, hVM1 clone 32 cells, a line of human neural stem cells, were characterized and subsequently transplanted in middle-aged Parkinsonian mice in order to examine cell replacement therapy as a treatment for PD. In vitro analyses revealed that these cells express standard dopamine-centered markers as well as others associated with mitochondrial and peroxisome function, as well as glucose and lipid metabolism. Four months after the transplantation of the hVM1 clone 32 cells, striatal expression of tyrosine hydroxylase was minimally reduced in all Parkinsonian mice but that of dopamine transporter was decreased to a greater extent in buffer- compared to cell-treated mice. Behavioral tests showed marked differences between experimental groups, and cell transplant improved hyperactivity and gait alterations, while in the striatum, astroglial populations were increased in all groups due to age and a higher amount of microglia were found in Parkinsonian mice. In the motor cortex, nonphosphorylated neurofilament heavy was increased in all Parkinsonian mice. Overall, these findings demonstrate that hVM1 clone 32 cell transplant prevented motor and non-motor impairments and that PD is a complex disorder with many influencing factors, thus reinforcing the idea of novel targets for PD treatment that tend to be focused on dopamine and nigrostriatal damage.